Case Report: Is the isolated bone change in advanced colorectal cancer necessarily malignant metastasis? - Xue, Huimin; Sun, Xin; Yang, Xiaomei; Chen, Wenjuan; Chen, Juan; Qu, Xiujuan; Chen, Ying; Qu, Jinglei (Frontiers in Oncology, 2025)
BackgroundRadiation osteitis (RO) is a bone-related complication following radiotherapy (RT), often characterized by atypical imaging features. It is challenging to distinguish RO from early bone metastasis (BM), potentially leading to inappropriate treatment. Therefore, establishing reliable diagnostic criteria for accurately identifying RO is essential for improving treatment outcomes in advanced colorectal cancer (CRC).Case descriptionTwo cases of advanced CRC patients with atypical isolated bone changes on imaging are presented. Both patients received standard chemotherapy and radiotherapy after surgery. Through comprehensive imaging studies, laboratory evaluations, and multidisciplinary team (MDT) consultations, the diagnosis of RO was confirmed instead of BM, thereby avoiding the need for an invasive pathological biopsy.ConclusionsThis case report highlights imaging features of RO and provides valuable insights into differentiating RO from BM by integrating medical history, laboratory findings, and imaging results.